The Relationship between Sex Offender Height and Pedophilic Interest. Issue 12 (2nd December 2017) - Levenson, Jill S.; Ackerman, Alissa R.
ABSTRACT: The current study examined the relationship between offender height and pedophilic interest (as measured by having a victim under 13 years old) in a sample of 22, 228 registered sex offenders in the United States. Results revealed that offenders with victims age 12 and under were, on average, nearly one-quarter inch shorter than offenders of adults, and .18 inches shorter than those with minor teen victims. Implications for future research about the biological etiology of child sexual abuse perpetration are discussed, including the role of adverse childhood experiences in the neurodevelopment of offenders.